Community Participation in Urban Open Innovation Projects : Case Study of the Innovation Intermediary Organization Forum Virium Helsinki - Keinonen, Ella (My University, 2025)
Master's thesis Subject: Geography Author(s): Ella Keinonen Title: Community Participation in Urban Open Innovation Projects Supervisor(s): Dr. Lauri Hooli, University of Turku & Dr. Ana Rita Amaral, Universidade de Coimbra Number of pages: 80 pages Date: 6.4.2025 This thesis investigates community participation facilitated by the innovation intermediary Forum Virium Helsinki (FVH) within urban open innovation projects in Helsinki. The aim is to understand the objectives of participation, the methods employed, and their relative success in fostering community participation. Using a qualitative case study approach and the Comparison of Participatory Processes (COPP) framework, the research provides an in-depth analysis of participatory practices across different project stages, their contextual determinants, and explores the key drivers and barriers influencing community participation in selected projects. The retrospective case study examines seven projects in detail through data and method triangulation, including ten interviews and a range of written materials such as reports, deliverables, evaluations, and publications. Findings are organized according to four project stages, acknowledging that participation objectives and approaches vary throughout the project cycle. The results show that both the extent and nature of community participation shift depending on the stage. Notably, engagement is strongest during the early phase, where needs, challenges, and preferences are gathered through tools like surveys and pop- up events, and during the implementation phase, where communities usually participate as test users. In contrast, participatory activities are more passive in the solution design and evaluation stages, which limits the inclusion of valuable insights from their perspective. A key finding is the predominance of consultation- and information-level participation across the examined projects, while co-creation, though frequently discussed, was rarely realized in practice. This study addresses a research gap by examining the practical methods used by innovation intermediaries to foster community participation. Ultimately, it contributes to a deeper understanding of how actors like FVH engage communities, offering valuable insights for improving participatory practices in future urban development initiatives.

Tässä opinnäytetyössä tarkastellaan asukkaiden osallistumista innovaatioiden välittäjäorganisaatio Forum Virium Helsingin (FVH) toteuttamissa urbaanin avoimen innovoinnin projekteissa Helsingissä. Tavoitteena on ymmärtää osallistamisen tavoitteita, käytettyjä osallistavia menetelmiä sekä niiden onnistumista asukkaiden osallistumisen edistämisessä. Tutkimus toteutettiin laadullisena tapaustutkimuksena, jossa hyödynnettiin osallisuusprosessien vertailuun kehitettyä COPP-viitekehystä (Comparison of Participatory Processes). Tutkimus tarjoaa syvällisen analyysin osallistavista käytännöistä eri projektivaiheissa sekä niitä ohjaavista kontekstuaalisista tekijöistä. Lisäksi se tarkastelee asukkaiden osallistumista edistäviä ja estäviä tekijöitä valituissa projekteissa. Retrospektiivisessä tapaustutkimuksessa analysoitiin yksityiskohtaisesti seitsemää projektia hyödyntäen triangulaatiota, joka koostui kymmenestä haastattelusta sekä monipuolisesta kirjallisesta aineistosta, kuten raporteista, arvioinneista ja julkaisuista. Tutkimuksen tulokset on jäsennelty neljän projektivaiheen mukaan, sillä osallistumisen tavoitteet ja lähestymistavat vaihtelevat projektin elinkaaren aikana. Tulosten perusteella asukkaiden osallistumisen laajuus ja luonne muuttuvat vaiheittain. Osallistuminen on aktiivisinta alkuvaiheessa, jolloin kartoitetaan tarpeita, haasteita ja toiveita esimerkiksi kyselyiden ja pop up -tapahtumien avulla, sekä toteutusvaiheessa, jossa asukkaat osallistuvat usein pilottikäyttäjinä. Sen sijaan ratkaisujen suunnittelu- ja arviointivaiheissa osallistaminen on passiivisempaa, mikä rajoittaa asukkaiden näkemysten ja kokemusten hyödyntämistä. Keskeinen havainto on, että osallistuminen jää tarkastelluissa projekteissa pääosin tiedottamisen ja kuulemisen tasolle, vaikka yhteiskehittämisestä puhutaan paljon. Käytännössä yhteiskehittämistä asukkaiden kanssa toteutettiin harvoin. Tämä tutkimus vastaa tunnistettuun tutkimusaukkoon tarkastelemalla käytännön osallistamismenetelmiä, joita innovaatioiden välittäjäorganisaatiot käyttävät asukkaiden osallistumisen tukemiseksi. Se tarjoaa syvempää ymmärrystä siitä, miten toimijat kuten FVH ottavat asukkaat mukaan kehittämistyöhön, ja antaa arvokkaita näkökulmia osallistavien käytäntöjen kehittämiseen tulevissa kaupunkikehityshankkeissa.
Keywords: community participation, innovation intermediary, open innovation project, participatory methods